Spiritual Leadership, Organizational Culture, and SME Performance: The Moderating Role of Honor Norms - Achmarul Fajar; Syaiful (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines how spiritual leadership and organizational culture influence the performance of micro, small, and medium enterprises (MSMEs), as well as how systems of honour norms as a form of informal governance moderate this relationship. Although previous research has emphasised the role of value-based mechanisms in shaping organizational performance, little attention has been paid to how informal institutions affect their effectiveness. Using survey data from 231 MSMEs operating in community-based contexts, this study applies partial least squares structural equation modelling (PLS-SEM) to test the direct and moderating effects. The results show that both spiritual leadership and organizational culture have a positive and significant influence on MSME performance, with organizational culture demonstrating a stronger effect. Furthermore, systems of honour norms strengthen the relationship between spiritual leadership and performance but do not moderate the relationship between organizational culture and performance. These findings indicate that the effectiveness of value-based organizational mechanisms is contingent on the presence of informal social enforcement mechanisms, although in an asymmetric manner. Specifically, leadership-based mechanisms are more sensitive to institutional contexts than organizational culture-based mechanisms, which tend to function as a more stable form of internal governance. This research contributes to the literature by integrating perspectives from organizational behaviour and institutional economics and affirms the role of informal governance as a boundary condition in shaping organizational performance in developing country contexts.